THE IMPACT OF MOBILE APPLICATIONS AND PODCASTS ON DEVELOPING LISTENING COMPREHENSION STRATEGIES IN EFL CLASSROOMS - Atamuradova Jasmina Jahongirovna, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Annotation: This paper investigates the effectiveness of contemporary digital resources—specifically, mobile apps, podcasts, and interactive platforms—in boosting the listening comprehension abilities of English as a Foreign Language (EFL) students. In  the  age  of  Mobile  Language  Learning  (MLL),  traditional  audio  resources  are gradually being replaced with high-quality digital materials. The study looks at how services like BBC Learning English, British Council Podcasts, and gamified apps like Duolingo assist both "top-down" and "bottom-up" methods to listening. This study demonstrates that digital technologies not only provide actual language input but also improve  learner  autonomy  and  motivation  through  a  qualitative  review  of  known pedagogical  frameworks  and  student  interaction  patterns.  The  findings  show  that introducing interactive platforms into the curriculum allows for personalized learning speeds and quick feedback, which reduces "listening anxiety" and improves long-term retention of material.